Emotion regulation in 7‐year‐old children with familial high risk for schizophrenia or bipolar disorder compared to controls – The Danish High Risk and Resilience Study – VIA 7, a population‐based cohort study. (27th August 2022) - Spang, Katrine Søborg; Hagstrøm, Julie; Ellersgaard, Ditte; Christiani, Camilla; Hemager, Nicoline; Burton, Birgitte Klee; Greve, Aja Neergaard; Rohr, Kirsten; Gantriis, Ditte; Vangkilde, Signe; Mors, Ole; Nordentoft, Merete; et al.
Abstract: Objectives: Emotion regulation is a predictor of overall life outcome. Problems of emotion regulation are associated with multiple psychiatric disorders and could be a potential treatment target for improving well‐being and functioning. Children at familial high risk of severe mental illness have a markedly increased risk of various psychopathology and constitute a group at significant risk of emotion regulation problems. Investigations of emotion regulation in children at familial high risk of severe mental illness are sparse. Methods: We applied an instrument for assessing emotion regulation, the Tangram Emotion Coding Manual (TEC‐M), to a population‐based cohort of 522 7‐year‐old children born to parents diagnosed with either schizophrenia or bipolar disorder and matched controls. The TEC‐M is an ecologically valid, clinician‐rated observational test measure of spontaneous emotion regulation. We aimed to compare emotion regulation between risk groups and to investigate associations between emotion regulation and psychopathology and daily life functioning, and between emotion regulation and an acknowledged questionnaire‐based dysregulation profile. Results: In this early developmental phase, we found no between group differences in emotion regulation. We found a significant but weak negative association between emotion regulation and both child psychopathology and the presence of a dysregulation profile on the Child Behavior Checklist and a weak positive association between emotion regulation and current level of functioning. Conclusions: These findings contribute to the understanding of emotion regulation in familial high‐risk children and further studies of emotion regulation in children at familial high risk of severe mental illness are warranted.